Production of functional platelet-like particles by the megakaryoblastic DAMI cell line provides a model for platelet biogenesis - Lev, Paola Roxana (2010)
The aim of this study was to evaluate cell maturation and the platelet production capacity of the megakaryoblastic DAMI cell line, to characterize platelet-like particles produced and to investigate the mechanisms involved in their production. DAMI cell maturation was induced by phorbol myristate acetate (PMA) and thrombopoietin (TPO). Expression levels of GATA-1, Fli-1 and NF-E2 were evaluated using real-time PCR and western blot. Platelet-like particles were characterized by the presence of GPIb and GPIIb by flow cytometry, while the soluble fragment of GPIb, glycocalicin, was detected by enzyme immunoassay. Dense and alpha granules were evaluated by mepacrine staining and thrombospondin-1 detection, respectively, and by electron microscopy. Functional capacity of platelet-like particles was studied by measuring P-selectin membrane after thrombin stimulation by flow cytometry and actin polymerization using phalloidin-FITC by immunofluorescence. We found that stimulation of DAMI cells with high concentration of PMA and TPO induced the expression of transcription factors GATA-1 and Fli-1 followed by an increase in the isoform a of NF-E2. Mature DAMI cells give rise to extensions resembling proplatelets and later, produce platelet-like particles expressing GPIIb and GPIb on their surface and containing dense and alpha granules, which were confirmed by electron microscopy. Platelet functionality was demonstrated by the increase in P-selectin membrane expression after thrombin stimulation and by their ability to spread on fibrinogen matrices. DAMI cell line induced to differentiate into mature megakaryocytes is able to produce functional platelets providing a suitable model to study the mechanisms involved in platelet generation.